Carbosilane dendrons with fatty acids at the core as a new potential microbicide against HSV-2/HIV-1 co-infection. Issue 44 (1st November 2017) - Guerrero-Beltrán, C.; Ceña-Diez, R.; Sepúlveda-Crespo, D.; De la Mata, J.; Gómez, R.; Leal, M.; Muñoz-Fernández, M. A.; Jiménez, J. L.
Abstract : The development of a HSV-2/HIV-1 co-infection in vitro model (a): dendrons prevented HIV-1 infection even if mucosal disruptions occur as a consequence of HSV-2 infection (b). Abstract : Herpes simplex virus type 2 (HSV-2) and human immunodeficiency virus type 1 (HIV-1) represent the two most frequent sexually transmitted infections (STI) worldwide. Epidemiological studies suggest that HSV-2 increases the risk of HIV-1 acquisition approximately 3-fold mainly due to the clinical and immunological manifestations. In the absence of vaccines against both STI, the development of new preventive strategies has become essential for further studies. We performed the screening of six novel polyanionic carbosilane dendrons to elucidate their potential activity against HSV-2/HIV-1 co-infection and their mechanism of action. These new nanoparticles are carbosilane branched dendrons from first to third generation, with palmitic or hexanoic fatty acids as the core and capped with sulfonate groups, named G1d -STE2Hx, G2d -STE4Hx, G3d -STE8Hx, G1d -STE2Pm, G2d -STE4Pm and G3d -STE8Pm. G3d -STE8Hx and G3d -STE8Pm carbosilane branched dendrons showed high viability. These dendrons also showed a great broad-spectrum antiviral activity, as well as a suitable efficacy against HIV-1 even if the mucosal disruption occurs as a consequence of HSV-2 infection. Our results exert high inhibition against HSV-2 and HIV-1 by blocking the entry of both viruses with the median effective concentration EC50 values in the nanomolar range. Additionally, G3d -STE8Hx and G3d -STE8Pm retained their anti-HSV-2/HIV-1 activity at different pH values. G3d -STE8Hx and G3d -STE8Pm dendrons may be potential candidates as dual-acting microbicides against HSV-2/HIV-1 co-infection.